Perbedaan Pengaruh Pasta Gigi Berbahan Dasar Hidroksiapatit dan Eugena caryophillus Terhadap Hipersensitifas Gigi - Risya Aulia; Dewi Liliany Margaretta; Rosalina Tjandrawinata (Jurnal Material Kedokteran Gigi, 2018)
Tooth hypersensitivity is a clinical condition that describes localized, non spontaneous pain, and arises when tooth is stimulated using thermal, chemical, and mechanical stimuli. The use of desensitizing agent such as hydroxyapatite and Eugenia caryophyllus can be used as home treatment that can relieve tooth hypersensitivity. Hydroxyapatite is an inorganic compound that makes up the hard tissues of the human body such as bone, dentine and tooth. Hydroxyapatite has a mechanism to decrease dental hypersensitivity by inducing remineralization of the teeth and close the open dentinal tubules. Eugenia caryophyllus is a material that is used in the field of dentistry and can reduce the pain of tooth hypersensitivity by suppressing nerve receptors in the perception of pain felt by the patient. The aim of this study is to determine the influence of hydroxyapatite-based toothpaste and Eugenia caryophyllus against tooth hypersensitivity. In this observational research, researcher give different type of toothpaste to two groups of research subjects and measure the changes in tooth sensitivity for 15 days. The value of tooth hypersensitivity before and after treatment is tested using Electric Pulp Test (EPT). Independent t-test shows the result of p value = 1.30 (p>0.05). It can be concluded that there is no significant difference between hydroxyapatite and Eugenia caryophyllus in relieving tooth hypersensitivity after being used for 15 days.